INTERNATIONAL ASSESSMENT SYSTEMS: PIRLS EXPERIENCE AND ITS SIGNIFICANCE - Xabibovna, Mashrapova Sevara (Research Focus International Scientific Journal, 2026)
This article analyzes the essence, methodological foundations, and specific features of international assessment programs — PIRLS and ePIRLS, which are vital components of the modern educational system. The study details the cognitive processes, text types, and task levels used to assess the reading literacy of primary school students. Particular emphasis is placed on the differences between the ePIRLS system, which develops information processing skills in a digital environment, and traditional assessment methods. Based on statistical data, the article substantiates the factors influencing student success, including the role of the home environment and parental involvement. The study concludes with practical recommendations for aligning the national education system with international standards and enhancing students' analytical thinking skills.